Consumo de alimento en cuyes desde gazapos hasta crecimiento machos y hembras en el ceypsa - Carlos Alfredo, Portilla Cadena (2016)
This research was conducted in the Technical University of Cotopaxi, Salache Bajo sector, in the Veterinary Medicine carrer where feed intake was determined in cuyes from gazapos to growth in the CEYPSA, knowing that this stage is the most important survival during their productive life, having as objective the identification, grouping by contemporary groups and animals´ phenotypic characteristics . The identification of cobayos is a method that allows data collection and know the by minors in relation to the particularity of each animal found in phenotypic characteristic; clustering allows us to determine the management for the entire contemporary group because in these management, demand, supply, and nutrient balances is very close between them. In handling the test it is started by selecting the animals in relation to their genotypic characteristics, obtaining (painted without swirl, painted with swirling, red, white, bayos) allowing us to determine depending on the differences in relation to animal consumption. Allowing to determine values used for feed conversion; the dry matter of each forage mixture where in the Kikuyo 16,45 MS, MS Ray Grass 17.64% MS, alfalfa with 14.8% MS, forage mixture 18.24% MS.